Studi Tahlili Hadis Abu Hurairah Tentang Amalan yang Melembutkan Hati - Rachmat Bin Badani Tempo (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This research aims to determine the content of Abu Hurairah's hadith regarding explanations of practices that can soften the human heart. This research is descriptive research using library methods and a Tahlili Hadith Study approach. The results of this research found several things. First, the hadith of practice that softens the heart is a hadith that is valid and can be practiced, because it was narrated from Abu Hurairah and Abu Darda. Even though both lines of hadith have weaknesses, these weaknesses are not serious, so they can strengthen each other. Second, the sabab wurud hadith of Abu Hurairah regarding practices that soften the heart is a complaint from one of his friends to the Prophet Muhammad. about his hard heart. Third, this hadith contains an explanation of practices that can soften a person's heart. As mentioned previously, this hadith was said by the Prophet Muhammad. on the basis of a friend's complaint about his hard heart. For this reason, Rasulullah saw. directing him to practice things that are the opposite of what he feels in his heart, namely by being kind and gentle towards weak people, especially orphans who need guidance, love and attention from other people for them.